Estrutura fina do espermatozóide de Mellita quinquiesperforata Leske (Echinodermata) do litoral norte do Brasil - MATOS, Edilson Rodrigues (2014)
The fine structure of the spermatozoon in the Mellita quinquiesperforata Leske, 1778 was studied. Collected from the Amazon region, were described by light and transmission electron microscopy. The spermatozoon consisted of a acrosome complex, nucleus, four to six mitochondria, two centrioles and flagellum. The acrosome was composed of a acrosome complex, the acrosomal vesicle and the subacrosomal space. The nucleus are composed by dense material. The middle piece contains 4-6 mitochondria which are arranged around the centrioles, the 9p+0, whose axoneme has the classic 9p+2 microtubular construction.